Associations of Novel Dietary and Lifestyle Inflammation Scores With Incident Colorectal Cancer in the NIH-AARP Diet and Health Study. Issue 3 (5th March 2020) - Byrd, Doratha A; Judd, Suzanne E; Flanders, W Dana; Hartman, Terryl J; Fedirko, Veronika; Agurs-Collins, Tanya; Bostick, Roberd M
Abstract: Background: Chronically higher inflammation, likely contributed to by dietary and lifestyle exposures, may increase risk for colorectal cancer (CRC). To address this, we investigated associations of novel dietary (DIS) and lifestyle (LIS) inflammation scores with incident CRC in the prospective National Institutes of Health–American Association of Retired Persons Diet and Health Study (N = 453 465). Methods: The components of our previously developed and externally validated 19-component DIS and 4-component LIS were weighted based on their strengths of associations with a panel of circulating inflammation biomarker concentrations in a diverse subset (N = 639) of participants in the REasons for Geographic and Racial Differences in Stroke Study cohort. We calculated the components and applied their weights in the National Institutes of Health-American Association of Retired Persons cohort at baseline, summed the weighted components (higher scores reflect a higher balance of proinflammatory exposures), and investigated associations of the scores with incident CRC using Cox proportional hazards regression. All statistical tests were two-sided. Results: Over a mean 13.5 years of follow-up, 10 336 participants were diagnosed with CRC. Among those in the highest relative to the lowest DIS and LIS quintiles, the multivariable-adjusted hazards ratios (HRs) and their 95% confidence intervals (CIs) were HR = 1.27 (95% CI = 1.19 to 1.35; P trend < .001) and 1.38 (95% CI = 1.30 to 1.48; P trend < .001), respectively. The associations were stronger among men and for colon cancers. The hazards ratio for those in the highest relative to the lowest joint DIS and LIS quintile was HR = 1.83 (95% CI = 1.68 to 1.99; P interaction < .001). Conclusions: Aggregates of proinflammatory dietary and lifestyle exposures may be associated with higher risk for CRC.